Resolving Engineering, Industrial and Healthcare Challenges through AI-Driven Applications - Muhamad Asvial; Teuku Yuri M. Zagloel; Ismi Rosyiana Fitri; Eny Kusrini; Yudan Whulanza (International Journal of Technology, 2023)
The recent technological advances have proven to be successful in facilitating various strenuous activities and improving daily life performance. Furthermore, the public has been amazed by the presence of Artificial Intelligence. Artificial Intelligence, often known as AI, is a type of technology in the field of computer science that has special abilities to solve problems. With its intelligence, which is said to be able to compete with human cognitive abilities, AI technology is, in fact, able to help a variety of human jobs, from easy to complex ones.The first work which is now recognized as AI was done by Warren McCulloch and Walter Pitts in 1943 as they proposed a model of artificial neurons. Later from that day, research in machine learning were florished. Therefore, Alan Turing who was an english mathematician proposed a test to asses the machine's ability to exhibit intelligent behavior equivalent to human intelligence. The word artificial intelligence was first adopted by American computer scientist, John McCarthy at the Dartmouth Conference for the first time. The finding of several computer language such as Fortran, LISP or COBOL marked the enthusiasm for AI at that time.The era of AI had several idle development along the way which called as AI winter in 1974 to 1980 and 1987-1993. This era refers to the time period where computer scientists dealt with a severe shortage of funding from government or companies. Until the year 1997, the IBM Deep Blue became the first computer to beat a world chess champion, the emergence of AI never went under. Companies like Facebook, Twitter and Netflix also started using AI deep learning, big data and artificial general intelligence since the 2006.     The applications of AI are vast, including in industrial automation, healthcare, transportation, finance, entertainment, and more. AI continues to develop along with advances in technology and research, with the ultimate goal of creating systems that have levels of intelligence and capabilities that increasingly approach human capabilities. Artificial intelligence also faces numerous debates regarding potential impacts on individuals. Although it could be risky, it's also offering a fantastic opportunity. It is estimated that the global Artificial Intelligence market will reach 267 billion dollars by 2027.